Cation distribution and magnetic behavior of Mg1 - XZn xFe2O4 ceramics monitored by Mössbauer Spectroscopy - Ounnunkad S. (2014)
The properties of magnesium ferrites, Mg1 - x Zn x Fe2O4 with 0.0 ≥ x ≥ 0.5, were investigated by means of powder X-ray diffraction, magnetization, Mössbauer spectroscopy, and scanning electron microscopy. The ferrites were prepared by conventional solid-state reaction using a mixed oxide method. All XRD patterns revealed only the monophasic spinel characteristic structure of MgFe2O4. The lattice parameters increased with the increasing of Zn content. Saturation magnetization (M S ) of the ferrites was discussed with respect to Zn substitution. M S values increased with Zn content up to x = 0.35 and then decreased thereafter. Mössbauer results showed Fe3 + ion distribution between tetrahedral and octahedral sites and the effect of Zn ions on ferrimagnetic order. The line-broadening of the Mössbauer spectra increased with substituting Mg with Zn ions due to disruption of the local magnetic order. The SEM micrographs of the sintered bodies showed irregular shape in the order of ∼5-6 μm. © Springer Science + Business Media, LLC 2006.